Impact of disease duration and β‐cell reserve on the efficacy of switching to iGlarLixi in adults with type 2 diabetes on glucagon‐like peptide‐1 receptor agonist therapy: Exploratory analyses from the LixiLan‐G trial. Issue 9 (28th May 2020) - Del Prato, Stefano; Frias, Juan Pablo; Blonde, Lawrence; Aroda, Vanita R.; Shehadeh, Niam; Saremi, Aramesh; Dex, Terry; Niemoeller, Elisabeth; Souhami, Elisabeth; Liu, Minzhi; Rosenstock, Julio
Abstract: Aim: To evaluate the efficacy of iGlarLixi by C‐peptide levels and duration of diabetes in an exploratory analysis of the LixiLan‐G study. Methods: LixiLan‐G was a 26‐week, randomized, open‐label study in adults with type diabetes (T2D) inadequately controlled while on a glucagon‐like peptide‐1 receptor agonist (GLP‐1 RA), with metformin, with or without pioglitazone and/or a sodium‐glucose co‐transporter‐2 inhibitor. This analysis investigated the efficacy of switching to iGlarLixi by fasting baseline quartile C‐peptide levels and baseline quartile of duration of T2D compared with continued GLP‐1 RA use. Results: Change in glycated hemoglobin (HbA1c) from baseline to week 26 was significantly greater with iGlarLixi compared with continued GLP‐1 RAs across all fasting C‐peptide quartiles (−1.00% to −1.06% vs. –0.23% to −0.54% range, respectively) and irrespective of all T2D duration quartiles (−0.94% to −1.07% vs. –0.25% to −0.50% range). A significantly greater proportion of participants in the iGlarLixi arm achieved an HbA1c of <7% across all C‐peptide quartiles (51%‐73% range) than in the GLP‐1 RA arm (19%‐32% range). The greatest reductions in HbA1c in participants receiving iGlarLixi were observed in those with the shortest duration of disease, although consistently greater than reductions observed with continued GLP‐1 RAs. Reductions in HbA1c were comparable across C‐peptide quartiles within the iGlarLixi arm. Conclusions: The results of this study suggest that iGlarLixi is an effective treatment option, irrespective of C‐peptide levels or duration of diabetes, in adults with insufficiently controlled T2D receiving GLP‐1 RAs.